Implementation of the Rapid Entire Body Assessment (REBA) Method in an Effort to Reduce Musculoskeletal Disorders (MSDs) in the Footwear and Automotive Industry - Sukapto, Paulus; Geovando Gita, Graemmy; Amanda, Gabriela; Liauw, Justin; Gunawan, Maisie; Fathurohman, Muhamad (Ann Publisher, 2025)
Background. This paper examines the impact of uncomfortable workplaces on absenteeism and employee complaints in the shoe and automotive industries. The risk of work-related accidents can be caused by several factors, such as unsafe actions resulting from unsuitable work positions for employees. Aims. This study analyzes the risk of MSDs interference among workers in the Material Inspection and Packing Department of PT X Shoe Company and PT Adyawinsa Stamping Industry (PT ASI). Method. The methods employed include direct observation in the workplace, visual documentation, in-depth interviews with workers, and measurements using the REBA. Result. The measurement results indicate that arranging materials on shelves and boxes on pallets has a REBA score that falls in the medium to high category, making it necessary to improve the working position as soon as possible. Conclusion. Improvement efforts are made to assistive devices, and directions are given to workers to improve their work posture. The results of work improvement using these tools will lead to a safer and more comfortable work environment. Implementation. This study proposes the application of anti-fatigue mats, improved air circulation, and work posture training to reduce ergonomic risks. With these interventions, employees can work more effectively, improving work comfort, reducing the risk of MSDs, and enhancing worker productivity.